2014
DOI: 10.3402/nano.v5.24381
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on the application of nanotechnology in photodynamic therapy for the treatment of melanoma

Abstract: Malignant melanoma is the most aggressive form of skin cancer and has been traditionally considered difficult to treat. The worldwide incidence of melanoma has been increasing faster than any other type of cancer. Early detection, surgery, and adjuvant therapy enable improved outcomes; nonetheless, the prognosis of metastatic melanoma remains poor. Several therapies have been investigated for the treatment of melanoma; however, current treatment options for patients with metastatic disease are limited and non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
50
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 111 publications
(180 reference statements)
0
50
0
Order By: Relevance
“…It has been applied to destruct selected tumors with clinical approval and several studies have confirmed that PDT is a feasible therapeutic option against early-stage cancer and co-therapeutic approach in late-stage cancer [4]. Typically, PDT involves a photosensitizer (PS), which can transfer energy to surrounding molecular oxygen to generate reactive oxygen species (ROS), primarily singlet oxygen ( 1 O 2 ), which can consequently induce cell apoptosis or necrosis and tissue destruction [5].…”
Section: Introductionmentioning
confidence: 99%
“…It has been applied to destruct selected tumors with clinical approval and several studies have confirmed that PDT is a feasible therapeutic option against early-stage cancer and co-therapeutic approach in late-stage cancer [4]. Typically, PDT involves a photosensitizer (PS), which can transfer energy to surrounding molecular oxygen to generate reactive oxygen species (ROS), primarily singlet oxygen ( 1 O 2 ), which can consequently induce cell apoptosis or necrosis and tissue destruction [5].…”
Section: Introductionmentioning
confidence: 99%
“…[73][74][75][76] Over the last decade, numerous nanoparticles have been developed for the in vivo tumor-targeted delivery of imaging agents or drugs. [77][78][79][80] We developed self-assembled HANPs that can be used as the tumor-targeted delivery system of photosensitizers for both photodynamic imaging and photodynamic therapy. [10] Because photosensitizers can simultaneously generate fluorescence for imaging and singlet oxygen for treatment upon irradiation, it may be useful as a theranostic system for combined diagnosis and therapy.…”
Section: Ha-based Nanoparticles For Small Molecular Drug Deliverymentioning
confidence: 99%
“…[1][2][3][4] In recent years, PDT has achieved rapid progress both in fundamental research [5][6][7][8] and clinic practice, [9][10][11] which makes it become the fourth minimal invasive therapy for cancer treatment following surgery, radiotherapy and chemotherapy. 12 PDT is based on the principle that light-activated photosensitizer can produce lethal cytotoxic active singlet oxygen ( 1 O 2 ) and other reactive oxygen species (ROS) to damage tumors and their surrounding vasculature when the tumor tissues uptaking the photosensitizer are irradiated with a specific wavelength light in the presence of tissue oxygen.…”
Section: Introductionmentioning
confidence: 99%